PDE-based image restoration using variational denoising and inpainting models - Barbu, Tudor; Ciobanu, Adrian; Luca, Mihaela (2014 18th International Conference on System Theory, Control and Computing (ICSTCC), 2014)
A PDE-based image restoration model is proposed in this paper. It aims to restore degraded images that are affected by both noise and missing zones. The considered restoration approach is based on two PDE variational techniques. The first variational method performs an efficient noise reduction, while the second variational model provides the image reconstruction. By using both variational models, one achieves a much better enhancement of the degraded image.